Mindfulness-Based Interventions for In-Patients With Schizophrenia Spectrum Disorders—A Qualitative Approach - Böge, Kerem; Karadza, Almira; Fuchs, Lukas M.; Ehlen, Felicitas; Ta, Thi Minh Tam; Thomas, Neil; Bajbouj, Malek; Hahn, Eric (Frontiers in Psychiatry, 2020)
In recent years, mindfulness-based interventions (MBI) have gained clinical relevance in the treatment of patients with schizophrenia spectrum disorders (SSDs). High symptom burden, long durations of hospitalization and high rehospitalization rates demonstrate the severity and cost-intensity of this disorder. MBIs have shown promising treatment outcomes in a small number of trials, primarily taking place in English-speaking countries. Through a qualitative approach the current study aims to explore mechanisms and processes of MBIs inpatients with SSDs as well as its applicability, acceptability and safety in a German university hospital setting. A qualitative design based on inductive content analysis with quantitative assessments were chosen. A semi-structured interview guide was developed by psychiatrists and psychologists to assess patient experiences, perceptions, thoughts, and feelings during and after taking part in an MBI. Twenty-seven interviews were conducted between September 2017 and October 2018 with inpatients diagnosed with paranoid schizophrenia or schizoaffective disorder. In addition, rater-based questionnaires, such as the Positive and Negative Syndrome Scale (PANSS), Montgomery Asberg Depression Rating Scale (MADRS), and Psychotic Symptom Rating Scales-Auditory Hallucination (PSYRATS-AH) were administered at baseline to collect clinical outcomes. Qualitative content analysis revealed effects in three domains: first a domain related to content with the core elements “detachment and rumination”, “presence and getting lost”, “non-judgment and judgment”, and a second domain main related to effects with “emotions”, “cognition”, and “symptom changes”. Third, a domain related to function was extracted, including the relevance of context and transferability. Overall, improvements concerning cognition, distress, and psychopathology were detected, while no adverse effects such as an increase in psychotic symptoms were revealed. As the first study of its kind, mechanisms and processes were explored as well as the applicability and safety of MBIs could be confirmed amongst a sample of German inpatients with SSDs. The results of this qualitative study are in line with recent findings on MBI in patients with psychotic disorders from other countries. In future research within this field focus should lay on the systematic study of MBIs in large samples, its treatment processes, outcomes, and effectiveness for inpatients within SSDs.